Use of off-label drugs and the prevalence of adverse reaction to drugs in the adult intensive care unit of a Brazilian public hospital - Lívia P. MOREIRA; Marjorie M. GUEDES; Eunice B. PERRAUD; Arnaldo A. PEIXOTO-JUNIOR; Eudiana V. FRANCELINO; Marta F. FONTELES (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2023)
Objective: To Identify the occurrence of adverse reactions to medications (ADR) in patients using off-label prescriptions admitted in an adult intensive care unit (ICU). Methods: Cross-sectional and prospective study evaluated the use of off-label medications and the appearance of ADR in an adult clinical ICU of a Brazilian hospital from March to Aug/2018. The prescriptions were classified as label, off-label, and unlicensed, and the NARANJO algorithm assessed ADR occurrence. The suspected cases of ADR were separated into label and off-label. Results: The prevalence of off-label use was 73.0%, with 73.9% prescribed after admission to the ICU. Regarding the category of off-label use, 23.6% were due to the volume of the diluent. The predominant drug classification was systemic antimicrobials, accounting for 16.8%. The PHD represented 68.7% of the off-label medicines. Sixty suspected ADR were identified in 26 patients registered with suspected ADRs, from that 85.0% resulted from the use of off-label medications. The most prevalent reactions were classified as probable (81.7%), and diarrhoea was the most frequent symptom. There was a significant association between the use of off-label drugs, PHD prescriptions, and the occurrence of ADR (p <0.05).Conclusion: The findings showed that the event of ADR was higher among off-label drugs and PHD prescriptions.